Synonymitaet im Text Eine Untersuchung an russischen Textbeispielen - Schuster, Rudolf (Slavistische Beitraege, 1995)
At the center of most of the contributions to the synonym was the paradigmatic relations between lexems, as I will show in a detailed research overview. Despite the abundant literature on this subject, little attention has been paid to questions of the nature, nature and functions of synonymous relationships in the text. The present work should therefore make it clear that only the analysis of the syntagmatic relations, for which I will use the terms "synonymy" and "synonymic" in contrast to the paradigmatic synonymy, will provide important insights into the contextual meaning constitution and the semantic structure of texts.